Critical temperature switch development for metallic magnetic calorimeters. (3rd April 2019) - Kim, S R; Jeon, J A; Kim, I; Kim, H L; Kim, S G; Kwon, D H; Lee, M K; Lee, H J; Kim, Y H
Abstract: We report the recent progress on critical temperature switch development for metallic magnetic calorimeters (MMCs). The superconducting planar coil of a micro-fabricated MMC is charged with a persistent current, which serves as the stable field current to magnetize the sensor material. Part of the Nb superconducting circuit is fabricated with an alloy of Nb and Ta (NbTa), another superconducting material with a transition temperature ( T C ) that is lower than that of Nb. A persistent current can be injected into the loop while lowering the temperature from above to below the T C of the NbTa switch. Resistance measurements of a sputtered film of a NbTa alloy with a Ta concentration of 62% showed a clear superconducting transition at 5.29 K. Using one of the completed MMC devices, the ability to use the T C switch for charging with a persistent current up to 120 mA was tested by means of magnetization measurements. The magnetization measurements recorded with a DC-SQUID were in good agreement with the calculated values in all tested cases with four different currents. These results indicate that an MMC can be charged with a persistent current as expected using the T C switch. This work is the first demonstration of the proposed T C switch in a complete MMC setup. Based on the present progress, future studies will investigate multi-channel operation and the development of a hybrid setup with an on-chip heater.